IPOs and Auditor Reputation: Evidence from Audit Firm Data Breaches - Alhusaini, Badryah; Lamoreaux, Phillip T.; Newton, Nathan J. (The Accounting Review, 2025)
ABSTRACT We use audit firm data breaches as time-varying, reputation-harming events to examine the value of auditor reputation—independent of actual audit quality—in the IPO process. We find that auditor data breaches are negatively associated with IPO offer price revisions. We demonstrate that this effect is due to an increase in institutional investors’ perception of information risk. Specifically, the effect is mitigated when other parties involved in the IPO reduce information risk themselves and when institutional investors are less likely to rely on audited financial information. In additional tests, we find that the impact of breaches on IPO offer price revisions is concentrated in breaches with greater severity, saliency, and frequency, consistent with institutional investors reacting to the announcement of the data breach rather than some other confounding factor. Collectively, our evidence suggests that IPO investors perceive time-varying reputational value of the external auditor, independent of changes in audit quality. JEL Classifications: G32; M42.